Mango (Mangifera indica L.) as a model for flavonoid studies - Baguer, Edmme A. (2024)
Nowadays, more and more people are turning to healthy eating, along with it, the consumption of active ingredients that have served as therapeutics in well-known traditional medicine. The objective of the work is a part of the abundant information that exists on the use of mango (Mangifera indica L.) to know its potential, understand where the research in recent years related to the use of secondary metabolisms of that mango is directed. This fruity, which could well be considered a model for all the benefits it offers. A search has been carried out using the PRISMA methodology to always use the same criteria in the SCOPUS, SciELO, REDALYC database and Google Academic as a search engine. In recent years, extraction methods have been improved and with it applications and studies with a scientific nature, which help explain its use in traditional medicine and project its future, although it is important to emphasize that there is still much to study and elucidate. Being faced with very large groups of phytochemicals with very specific actions, where bioavailability is low and must be taken into account when it comes to experiments and in vivo treatments.